Do ônus da prova à luz do processo penal democrático - Lorena Souto Tolentino (2019)
The following dissertation analyzes the burden of proof in the Brazilian criminal procedureaiming to instrumentalize it in the construction of a democratic structure for the jurisdictionalexercise, in accordance with the principles of the Rule of Law. The 1988 Constitution insertedin the Brazilian criminal prosecution, until then ruled by the Code of Criminal Procedure of1941, inspired by Italian fascist legislation, several principles guarantors of human dignity. Oneof these principles is the presumption of innocence that, in addition to being the structural basisof the criminal prosecution, has important consequences in the field of evidence. Because ofsuch importance, the text analyzes this principle under the historical, legislative and conceptualperspectives, and through this analysis, finds the constitutional foundations for the distributionof the burden of proof in the criminal process. In order to enable a more complete understandingof this institute under the perspective of democratic constitutionalism, some conceptual andlegislative aspects of the burden of proof in criminal proceedings are accentuated. Then, theresults of jurisprudential research are shown, which demonstrate that the burden of proof in theBrazilian judiciary is not analyzed under the influence of the constitutional provisions. Finally,in order to complement the results already obtained, from the analysis of the hermeneutic theoryof Gadamer, the research delineates the language character of the proof, which, analyzed withthe guarantee of the presumption of innocence guarantees the democracy in the prosecution andallows to conclude that the burden of proof in the criminal proceeding must be of theprosecution, which must present evidence attesting to the occurrence of a crime and shows thearguments that will delimit the understanding of the evidence in the sentence.